Interlevel absorption of electromagnetic waves by nanocrystal with divalent impurity - Boichuk, V.I.; Leshko, R.Ya. (Condensed Matter Physics, 2014)
The energy spectrum of central divalent impurity is calculated using the effective mass approximation in a spherical quantum dot (QD). The dipole moment and oscillator strength of interlevel transition is defined. The dependence of linear absorption coefficient on the QD size and electromagnetic frequency is analyzed. The obtained results are compared with the results of univalent impurity. У рамках методу ефективної маси обчислено спектр центральної двовалентної домiшки у квантовiй точцi (КТ) сферичної форми. Визначено дипольнi моменти та сили осциляторiв мiжрiвневих переходiв. Проаналiзовано залежнiсть лiнiйного коефiцiєнту поглинання електромагнiтних хвиль вiд розмiрiв КТ та частоти падаючої хвилi. Проведено порiвняння з вiдповiдними результатами для одновалентної домiшки.